Respuesta :
Respuesta:
X= {-7, 10}
Explicación paso a paso:
[tex]x^{2} - 3X - 70 = 0[/tex]
X -10 = -10X
X 7 = 7X
_____
- 3X
(X-10) (X+7)
X = 10
X = -7
X= {-7, 10}
Explicación paso a paso:
[tex] {x}^{2} - 3x - 70 = 0[/tex]
Puedes aplicar la fórmula general
[tex] \frac{ - b \frac{ + }{ - } \sqrt{ {b}^{2} - 4ac } }{2a} [/tex]
tenemos que
[tex]a = 1 \\ b = - 3 \\ c = - 70[/tex]
[tex] \frac{ - ( - 3) \frac{ + }{ - } \sqrt{ {( - 3)}^{2} - 4(1)( - 70) } }{2(1)} = \\ \frac{ 3 \frac{ + }{ - } \sqrt{ 9 + 280 } }{2} = \\ \frac{ 3 \frac{ + }{ - } \sqrt{ 289 } }{2} = \\ \\ \frac{3 + 17}{2} = \frac{20}{2} = 10 \\ \\ \frac{3 - 17}{2} = \frac{ - 14}{2} = - 7[/tex]
Ahora tenemos ambas raÃces.
[tex]x = 10 \\ x - 10 = 0[/tex]
[tex]x = - 7 \\ x + 7 = 0[/tex]
Verificacion
[tex](x - 10)(x + 7) = \\ {x}^{2} + 7x - 10x - 70 = \\ {x}^{2} - 3x - 70[/tex]
SALUDOS